Improving Student Learning Outcomes in The Legal Protection and Law Enforcement Materials Through Numbered Heads Together Cooperative Learning Model - Atsar, Abdul; Tasum, Tasum (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The purpose of this study was to find a solution to the problem in applying the NHT (Numbered Heads Together) cooperative learning model to improve student learning outcomes in Class XII Social Studies Major of SMA Mathla’ul Anwar High School Batujaya Karawang. This study used a classroom action research method. The study was conducted in three cycles and each cycle consists of 4 steps, namely planning, acting/implementing, observing, and reflecting. The results of the study show students' improvement in understanding the legal protection and law enforcement materials after the implementation of NHT cooperative learning model. By using the NHT model, the students find it easier to understand the concepts that used to be considered difficult. Before implementing the model, the understanding level of the students at SMA Mathla’ul Anwar Batujaya Karawang was relatively low because some students’ scores were below the minimum completeness criteria. After the actions in the three cycles were completed, the student learning outcomes increase. The students’ average score before the treatment was 60.16. It increased to 68.25 in cycle 1, 72.50 in cycle 2, and 80.25 in cycle 3. This increase indicates that the NHT model can help the students improve their understanding. In the learning process using this model, the students feel that they are systematically guided in understanding the materials. Moreover, it helps the students in improving their ability to explain the learning materials and to provide examples on the legal protection and law enforcement materials in the learning process using the NHT cooperative learning model.